Continuous propionic acid production with Propionibacterium acidipropionici immobilized in a novel xylan hydrogel matrix. (December 2015) - Wallenius, Janne; Pahimanolis, Nikolaos; Zoppe, Justin; Kilpeläinen, Petri; Master, Emma; Ilvesniemi, Hannu; Seppälä, Jukka; Eerikäinen, Tero; Ojamo, Heikki
Highlights: Cell immobilization possibilities of novel xylan-based hydrogel are introduced. Continuous fermentation of P. acidipropionici with packed immobilization is studied. Very high cell density within the immobilization material is achieved. Abstract: The cell immobilization potential of a novel xylan based disulfide-crosslinked hydrogel matrix reinforced with cellulose nanocrystals was studied with continuous cultivation of Propionibacterium acidipropionici using various dilution rates. The cells were immobilized to hydrogel beads suspended freely in the fermentation broth or else packed into a column connected to a stirred tank reactor. The maximum propionic acid productivity for the combined stirred tank and column was 0.88 g L −1  h −1 and the maximum productivity for the column was determined to be 1.39 g L −1  h −1 . The maximum propionic acid titer for the combined system was 13.9 g L −1 with a dilution rate of 0.06 h −1 . Dry cell density of 99.7 g L −1 was obtained within the column packed with hydrogel beads and productivity of 1.02 g L −1  h −1 was maintained in the column even with the high circulation rate of 3.37 h −1 .